2018
DOI: 10.1111/lit.12155
|View full text |Cite
|
Sign up to set email alerts
|

A forest‐based environment as a site of literacy and meaning making for kindergarten children

Abstract: This study analyses the valued school experiences of 15 fiveand six-year-old Canadian children, through their creation of multimodal texts. Throughout the school year, the students spent a large portion of each school day in the expansive forest on the school grounds, and their texts revealed their significant interest in this natural outdoor environment. Specifically, the data revealed that the outdoor space provided a context where the children could engage with each other and the environment in meaningful, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
(18 reference statements)
1
16
0
1
Order By: Relevance
“…The majority of the studies were conducted in the USA (n = 11) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], Australia (n = 5) [41][42][43][44][45] and Canada (n = 4) [46][47][48][49]. Three studies each were conducted in Norway [50][51][52], Sweden [53][54][55], and the United Kingdom [56][57][58].…”
Section: Geographical Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies were conducted in the USA (n = 11) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], Australia (n = 5) [41][42][43][44][45] and Canada (n = 4) [46][47][48][49]. Three studies each were conducted in Norway [50][51][52], Sweden [53][54][55], and the United Kingdom [56][57][58].…”
Section: Geographical Locationmentioning
confidence: 99%
“…Of the qualitative studies, the majority of studies (n = 4) used observational methods only [40,44,45,51] or (n = 2) observation and interviews (structured or semistructured) [39,52]. One study used interviews and teacher case studies [58], n = 1 used a combination of focus groups, interviews, observation, and artefact collection [49], n = 1 used a combination of interviews and surveys [61] and n = 1 used a combination of photo preference, drawings from children and interviews [37].…”
Section: Study Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the acquisition of competencies and the ability to learn constantly require a correct interaction with the environment to be able to construct one's knowledge [17]. Streelasky's [22] revealed that outdoor space provided a context in which children could interact with each other and the environment in meaningful, creative, and collaborative ways, as well as contributing to our understanding of young children's ability to share their thoughts and the power of alternative learning spaces.…”
Section: Outdoor Educational Activities: Definition and Benefitsmentioning
confidence: 99%
“…cl. Competencia en comunicación lingüística: Fomentando las destrezas y estrategias comunicativas para la lectura, la escritura, el habla, la escucha y la conversación a través de las diferentes modalidades que ofrece el juego cooperativo con temática de respeto y cuidado por el medio ambiente (Lieberman y Hoody, 1998;O'Brien, 2009;Streelasky, 2019).…”
Section: Propuesta Curricularunclassified